Analisis Hukum Pembiayaan Kesehatan Berbasis Teknologi Fintech serta Implikasinya terhadap Regulasi, Aksesibilitas, dan Keberlanjutan Sistem Kesehatan Nasional - Baginda Zulfikar; Marice Simarmata (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2025)
This study aims to examine the legal aspects of the Aceh People's Health Insurance Program (JKRA) by analyzing it as a hybrid between an insurance agreement and a social insurance agreement. The method used is a normative juridical approach, with qualitative analysis based on relevant laws and legal concepts. Data sources consist of primary, secondary, and tertiary legal materials. The results show that JKRA has two main characteristics. On the one hand, JKRA fulfills the elements of an insurance agreement, such as the existence of an insurer and an insured, premium payments, protection against risks, and the uncertainty of insured events. On the other hand, JKRA also reflects the characteristics of social insurance, namely being mandatory, non-profit-oriented, managed by the government, and applying the principle of mutual cooperation through a cross-subsidy mechanism. This dual character indicates that JKRA is a unique form of regional health insurance scheme that integrates private and social approaches. However, in its implementation, there are a number of legal issues that require serious attention. Some of the main problems found include the need for regulatory harmonization between JKRA and the National Health Insurance (JKN), ensuring the sustainability of funding through the Aceh Revenue and Expenditure Budget (APBA), and alignment with national health policies, especially after the enactment of Law Number 17 of 2023 concerning Health and Government Regulation Number 28 of 2024. Therefore, comprehensive legal regulations are needed so that the implementation of JKRA can run optimally and in line with the integrated national health insurance system, ensuring the sustainability of health services for the people of Aceh in a fair and sustainable manner.